Enabling participation for disabled young people: study protocol - Penelope Carroll; Karen Witten; Octavia Calder-Dawe; Melody Smith; Robin Kearns; Lanuola Asiasiga; Judy Lin; Nicola Kayes; Suzanne Mavoa (BMC, 2018)
Abstract Background Participation in community life is vital for health and wellbeing, promoting a sense of belonging, networks of social support and opportunities for physical activity. Disabled young people have lower levels of mobility and participation in recreational activities (physical, social and cultural), education and employment, than their peers without disabilities. This has implications for their health and wellbeing and life course opportunities. Previous research on the participation levels of disabled young people has primarily relied on parent/caregiver reports and been oriented to home and school environments. This study investigates how physical and social environmental factors cohere to support or restrict the everyday mobility and participation of disabled young people. Methods/design The study is located in Auckland, Aotearoa/New Zealand (NZ). Participants comprise 35 young people aged 12-25 years with mobility, vision or hearing impairments. A mixed-methods research design combines objective (global positioning systems, accelerometers, geographical information systems) and self-report measures (travel diaries, and questionnaires) to assess young people's mobility and levels of participation in leisure/educational and employment activities with in-depth interviews exploring their everyday experiences of inclusion/exclusion, and factors enabling or constraining community participation. Parents/caregivers and disability sector key informant viewpoints on the community participation of disabled young people have also been gathered through in-depth interviews. Follow-up workshops with young people and parents/caregivers will identify pathways to increase participation and challenge current disabling practices. Discussion This study looks beyond barriers in the physical environment to the interplay of personal, social and physical factors that enable or constrain the community participation of disabled young people. In keeping with the study's overarching goal of increasing opportunities for effective community participation and full citizenship of disabled young people, research methods were applied flexibily - negotiated and adapted to maximise each young person's participation in light of their abilities and preferences.